The Effectiveness of the Communicative Approach in Teaching Uzbek to Foreign Students (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the content, methodological foundations and effectiveness of the communicative approach in teaching Uzbek to foreign students. Since the Uzbek language taught to foreign audiences as a second or foreign language, the use of methodological methods, interactive exercises, situations close to real communication, and digital platforms aimed at developing communicative competence illustrated with practical examples. The results of the study show that the communicative approach increases the speech activity of foreign students, strengthens their motivation, and is highly effective in preparing them for real communication